Study of Epidemiology of Toxoplasmosis in Hemodialysis Patients in Baghdad Hospitals - Abdul-Aziz, Ayser; Zghair, Khawla (Iraqi Journal of Science, 2023)
This study aims to assess some seroprevalence of toxoplasmosis in chronic renal failure (CRF) patients undergoing hemodialysis in dialysis centers in some Baghdad hospitals, by testing the blood samples with enzyme linked Immunosorbant assay (ELISA) IgG and IgM, to determine the incidence of toxoplasmosis in hemodialysis patients. Hemodialysis patients infected with Toxoplasma. gondii were appeared with 129(32.25%) seropositive anti-Toxoplasma IgG. The age groups (43-51) year and (52-60) years of hemodialysis patients showed the highest percentage of anti-Toxoplasma gondii antibodies. An increase of the seropositivity rate was detected with increasing length of time on hemodialysis treatment. Females had the highest significant percentage of anti-Toxoplasma IgG 72 (55.81%) than males 57 (44.18%). Domestic poultry breeder had high percentage 71(55.03%) and 8 (57.14%) of anti-Toxoplasma (IgG+&IgM+) antibodies respectively in comparison with patients who do not breed domestic poultry.